Molecular docking and dynamics simulation to screen interactive potency and stability of fungicide tebuconazole with thyroid and sex hormone‐binding globulin: Implications of endocrine and reproductive interruptions. Issue 10 (25th February 2021) - Abdi, Sayed Aliul Hasan; Alzahrani, Abdulaziz; Asad, Mohammad; Alquraini, Ali; Alghamdi, Adel Ibrahi; Sayed, Shabihul Fatma
Abstract: Tebuconazole is a widely used fungicide in agriculture, and it may easily enter in the human food chain. In addition, tebuconzaol skin permeation coefficient (Log Kp) is −5.55 cm/s and it does not violate Lipinski's rule. It may mimic as a ligand for various endocrine and reproductive receptor leading to toxicological response or disease manifestation. We studied interactive potential of tebuconazole with thyroid and sex hormone‐binding globulin. The main methods for this in silico analyses are molecular docking and molecular dynamic (MD) simulation. This paper explores how agriculture fungicide tebuconzaol exposure can be a risk for endocrine and reprotoxicity due to its stable interactive potency with thyroid and sex hormone‐binding globulin (2CEO and 1D2S). Thyroid impairment is one of the most common endocrine issues in human health. In molecular docking analyses, tebuconazole exhibited binding potency of −6.28 kcal/mol with 2CEO compared to its native ligand thyroxin and inhibitor propylthiouracil which had the binding potency of −9.9 and −4.49 kcal/mol, respectively. The binding score of tebuconzaol with 1D2S was found to be −7.54 kcal/mol compared to native ligand dihydrotestosteron and inhibitor aminoglutethimide which exhibited the binding score of −6.84 and −11.41 kcal/mol, respectively. Therefore, each complex was subjected to MD simulation for comparative assessment of physical movement. The root mean square deviation (RMSD), root mean square fluctuation (RMSF), Radius of Gyration and hydrogen bonding exhibited that fluconazole had stable binding pattern with 2CEO and 1D2S which was almost similar to native ligand and its inhibitor. Study revealed that tebuconazole may lead to potent endocrine and reproductive disruptions. Abstract : Tebuconazole has possible efficacy to upset thyroid and sex hormone‐binding globulin by accruing the protein binding sites, acting as a blockade, and not engaging innate ligands to interact with their proteins. Hormones play important roles in the body homeostasis, and such stable interactions of tebuconazole can prompt hormonal imbalances and ultimately the endocrine and reprotoxicities.